Electrospinning process parameters optimization for biofunctional curcumin/gelatin nanofibers. (23rd March 2020) - Kanu, Nand Jee; Gupta, Eva; Vates, Umesh Kumar; Singh, Gyanendra Kumar
Abstract: Electrospinning has received wide attention for the preparation of uniform diameter nanofibers (ranging from 5 nm to several hundred nanometers) in films with random as well as aligned fashions of the fibers of various materials for use in biomedical applications. Electrospinning research has provided an in-depth understanding of the preparation of light weight, ultrathin, porous, biofunctional curcumin/gelatin nanofibers having applications in wound dressing, drug release, tissue engineering, etc. In the first half of this article, prior research on electrospun curcumin/gelatin nanofibers is reviewed in depth with nanofibers being desired due to their low diameters since these would have then large surface area to volume ratio and enough film porosity as well as improved mechanical (tensile) strength so that when prepared as mats these nanofibers (having high biocompatibility) could be used for sustained release of curcumin and oxygen to wounds during healing. The synthesis of ultrathin nanofibers (having minimum average diameter) is not a simple task unless numerical investigation is carefully done in the first half of this research article. The authors research described here examined the effects of critical process parameters (in the second half of the paper) such as distance between the spinneret and collector, flow rate, voltage and solution viscosity, on the preparation of uniform and ultrathin nanofibers using scanning electron microscopy (SEM) for characterization of the nanofibers. A 2 k factorial design of experiment was found to be a suitable and efficient technique to optimize the critical process parameters used in the preparation of the biofunctional nanofibers with the purpose of having applications in the treatment of problematic wounds such as diabetic chronic ulcers. After parametric investigation, the distance, flow rate and voltage when taken together, were found to have the most significant contributions to the preparation of minimum diameter nanofibers. The primary objective of this research was fulfilled with the development of ultrathin curcumin/gelatin nanofibers having a 181 nm (181 ± 66 nm) average diameter using the optimized setting of a solution having 1.5% gelatin, and 1% curcumin in 10 ml of 98% concentrated formic acid, with the electrospining unit having a voltage of 10 KV, distance from the spinneret to collector drum of 15 cm, flow rate of 0.1 ml h −1, viscosity of 65 cP and drum collector speed of 1000 rpm. However, the lowest average diameter of nanofiber was measured around 147 nm (147 ± 34 nm) which was prepared at a higher voltage, such as 15 KV (at 10 cm distance, 0.15 ml h −1 flow rate and 65 cP viscosity) using the solution. The design of this research paper is based on the view that merely optimization of biofunctional nanofibers may not fully satisfy researchers/engineers unless they are also provided with sufficient information about (a) the entire electrospinning mechanism (numerical investigations of the mechanism) to have better control over preparation of ultrathin nanofibers, and (b) applications of the resulting ultrathin biofunctional nanofibers while fabricating nanofibrous mats (as used now-a-days) for sustained release of curcumin during the critical hours of wound healing and other biomedical applications.